绕口令对丹大汉语教育专业2022届学生的发音准确性分析 - Anatashya, Shintya; Afrimonika, Yoanna; Khiong, Bun Yan (Confucius Institute Universitas Sebelas Maret, 2024)
Tongue twisters are a fun way to improve students' learning of Chinese pronunciation. When students say tongue twisters, they must do so quickly and with accurate pronunciation. Through this study, the author wants to know whether tongue twisters can effectively improve students' pronunciation accuracy and how interested students are in tongue twisters. In addition, the main purpose of this research is to train basic mastery of Mandarin pronunciation and improve new students' pronunciation. The author’s research subjects are the 2022 students majoring in Chinese education at the Faculty of Teacher Education, Tanjung Pura University. The author used test and questionnaire methods to collect research data. The author uses simple initial consonants such as b, p, d, and t for research. So the author chose the tongue twisters of